Luminescent nanohybrids based on silica and d-f heterobimetallic silylated complexes: new tools for biological media analysis - Sábio, Rafael Miguel [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The design of heterobimetallic luminescent complexes has gained growing interest in recent years due to their unique photophysical properties. More specifically, the development of heterobimetallic complexes using d-block chromophores to sensitize the near-infrared (NIR) emission of lanthanide complexes (such as Nd(III) and Yb(III)) has received significant attention taking into account their longer emission wavelengths and the interest of the NIR emission which penetrates human tissue more effectively than UV light. These properties give them potential applications in medical diagnostics or biomedical assays. Transitions to excited state levels of transition metal complexes occurring in the visible and characterized by large absorption coefficients, could efficiently sensitize f-f levels of Ln(III) ions. In this work new d-f heterobimetallic complexes containing silylated ligands were prepared supported on silica materials. [Ru(bpy)2(bpmd)]Cl2 (labeled Ru), [Ru(bpy)(bpy-Si)(bpmd)]Cl2 (labeled RuL) and [Ln(TTA-Si)3] (labeled LnL3) and d-f heterobimetallic complexes, Ru—LnL3 and Ln—RuL (Ln = Nd3+, Yb3+) were prepared. Structural characterization was carried out by Raman Scattering, 1H and 13C NMR spectroscopies. Results obtained from 1H-13C HMBC and HSQC correlation NMR spectra confirm the formation of proposed complexes. Photophysical properties studies highlight the efficiency of Ru—Ln energy transfer processes in NIR-emitting lanthanide complexes mediated by conjugated bridging ligand (2,2'-bipyrimidine). Lifetime measurements were carried out and values of quantum yield for energy transfer (ET) between 30 and 84 % could be evaluated. ET of 73.4 % obtained for the Yb—RuL complex is the largest value reported for Ru(II)—Yb(III) heterobimetallic complexes so far. Grafting on different silica matrix was also demonstrated. SiO2-Ru, SiO2-NdL3 and SiO2-YbL3 nanohybrids were obtained with grafting efficiencies from 0.08 to 0.18 mmol g-1 of silica. SiO2-RuNd and SiO2-RuYb were performed from simultaneous grafting of ruthenium and lanthanides silylated complexes. Grafting efficiencies from 0.10 to 0.16 were obtained. ET of 40 and 27.5 % were obtained from SiO2-RuNd and SiO2-RuYb, respectively. The higher values observed for the Nd(III) nanohybrid is well explained by the matching of donor and acceptor energy levels. SiO2-RuYbL3, SiO2-YbRuL, SiO2 d-YbRuL and SiO2-NdRuL were carried out from grafting of d-f heterobimetallic silylated complexes. Grafting efficiencies from 0.03 to 0.17 were obtained. Luminescent properties from these nanohybrids were similar to the free complexes. However the SiO2-YbRuL and SiO2 d-YbRuL showed distinct luminescent profiles compared with the free Yb—RuL. The grafting inside the mesoporous channels may prevent luminescent desactivation processes comparing to the dense silica matrix. The photophysical properties associated with the morphology and stability of the mesoporous silica matrix allow suggesting these new NIR luminescent nanohybrids as nanoprobes or nanomarkers in biomedicine.

Le design de complexes luminescents hétérobimétalliques a suscité ces dernières années un intérêt croissant en raison de leurs propriétés photophysiques uniques. Dans ces complexes de lanthanide (Nd (III) et Yb (III)) associé à des chromophores du bloc d, la forte émission des métaux de transition dans le visible est utilisée pour sensibiliser de façon efficace les niveaux f-f des lanthanides(III) qui émettent à leur tour dans le visible ou l’IR selon les terres rares. Plus spécifiquement l’attention s’est focalisée sur le développement de complexes hétérobimétalliques d-f pour l’émission dans le proche infrarouge (NIR). En effet le proche infrarouge, comparé à l’UV, pénètre plus facilement les tissus biologiques humains notamment la peau. Bien que de telles propriétés confèrent à ces complexes bimétalliques un fort potentiel pour le diagnostic médical, aucun complexe hétérobimétallique d-f greffé de façon covalente à une matrice de silice n’a été décrit. Dans ce travail de nouveaux complexes hétérobimétalliques d-f contenant des ligands silylés ont été préparés et greffés sur la silice. Les complexes monomères [Ru(bpy)2(bpmd)]Cl2 (noté Ru), [Ru(bpy)(bpy-Si)(bpmd)]Cl2 (noté RuL) et [Ln(TTA-Si)3] (noté LnL3) et les complexes hétérobimétalliques d-f Ru-LnL3 et Ln-RuL (Ln = Nd3+, Yb3+) ont été préparés. La caractérisation des complexes a été effectuée par spectroscopie Raman, RMN 1H et 13C RMN. Les spectres RMN 1D 1H et 13C NMR ainsi que 2D de corrélation HSQC confirment les structures proposées. L’étude des propriétés photophysiques met en évidence l’émission de l’élément lanthanide dans le proche infrarouge ainsi que l'efficacité du processus de transfert d'énergie Ru-Ln qui est facilité par le ligand (2,2'-bipyrimidine). Les mesures de durée de vie et de rendement quantique (ET) pour le transfert d'énergie indiquent des valeurs remarquables comprises entre 30 et 84 %. La valeur du rendement quantique (ET) du complexe d'Yb-RuL, 73,4 %, est à ce jour la plus grande valeur rapportée pour un complexe hétérobimétallique Ru (II)-Yb (III). Le greffage sur différentes matrices de silice, mésoporeuse SiO2 ou dense SiO2 d, a été réalisé. Les nanohybrides SiO2-RuL, SiO2-NdL3 et SiO2-YbL3 ont été obtenus avec des taux de greffage allant de 0,08 à 0,18 mmol de complexe par gramme de silice. SiO2-RuNd et SiO2- RuYb ont été obtenus par greffage simultané des complexes silylés monomères de ruthénium et de lanthanide, des taux de greffage de 0,10 à 0,16 mmol.g-1 ont été obtenus, respectivement. Les rendements quantiques ET de transfert d’énergie des nanohybrides SiO2-RuNd et SiO2-RuYb sont respectivement de 40 and 27,5 %. La valeur remarquable obtenue pour le nanohybride impliquant le néodyme, SiO2-RuNd, s’explique par bonne adéquation entre les niveaux d’énergie du donneur et de l’accepteur. Les nanohybrides SiO2- RuYbL3, SiO2-YbRuL, SiO2d-YbRuL et SiO2-NdRuL ont été obtenus par greffage des complexes silylés hétérobimétallic d-f élaborés dans ce travail, les taux de greffage, de 0,03 à 0,17 mmol.g-1 permettent d’envisager une fonctionnalisation chimique ultérieure de ces nanoobjets. Les propriétés de luminescence de ces nanohybrides sont similaires à celles des complexes non greffés hormis pour SiO2-YbRuL and SiO2d-YbRuL qui présentent des profils de luminescence différents comparés au complexe libre Yb—RuL. Le greffage à l'intérieur des pores de la silice pourrait éviter le processus de désactivation de la luminescent contrairement au greffage sur la matrice de silice dense. Les propriétés photophysiques associées à la morphologie et à la stabilité de la matrice de silice mésoporeuse permettent d’envisager l’utilisation de ces nouveaux nanohybrides luminescents dans le proche infrarouge comme nanosondes ou nanomarqueurs de systèmes biologiques.
Nanohybrides luminescents à base de silice et de complexe hétérobimétalliques d-f silylés: de nouveaux outils d'analyse des milieux biologiques
Keywords: Metallic complexes; Rare earth metals; Mesoporous materials; Silica; Luminescence